Mahfuz: â€œBeginningâ€ not the â€œEndâ€ - Diab, Gihan (Richtmann Publishing, 2012)
After more than a century we continue to discuss about the great pioneer of the Arabic literature. Naô€ƒ·ô€†¯b Maô€™fô€‡Œô€š© identified bysome critics â€œThe prince of the Arabic novelâ€, by others â€œThe father of realismâ€ and â€œSon of the Egyptian Landâ€. Actually, Iâ€™d prefer,specially at this time, if we call him â€œThe Arabic literature ambassadorâ€: his talent, dedication, intelligence and his strong belongingemotion to the alleys of the Old Islamic Cairo have led him to the whole world. But if Maô€™fô€‡Œô€š© has arrived to the globalism obtaining theNobel 1988, it would be unfair overlook the efforts the his ancestors or ignore the new generation of Arab writers. In other words, I thinkthat Maô€™fô€‡Œô€š© is to be considered the â€œbeginningâ€ not the â€œendâ€ of a new reciprocal estimation between the Arabic and the other literatures.With â€œBeginning and endâ€ Maô€™fô€‡Œô€š© has discovered the way to compose his most great Trilogy: according to some critics â€œBeginning andendâ€ is well thought-out the prehistory of his magnum opus.